Advanced educational content with modular production system MPS - von Terzi, Eckhard (2014)
Working in the industry is complex. This was found early last century Frederick W. Taylor , so he dedicated himself to breaking down work in phases until it was only necessary to perform a sequence of movements that few workers had to practice to achieve maximum productivity . Thus was born the concept of " Taylorism " and at that time , he also claims that Ford said, though never confirmed , that the customer could buy any car, if it is a Ford and is black. Meanwhile not only we are never satisfied with black cars. Rather we tend to customize our cars growing , acquiring additional equipment such as air conditioning , heating seats , practicable ceilings , fog lights , navigation systems or ski . But the trend towards individualization is not limited to cars . It also affects other areas of our lives , whether housing , furniture or clothing. To all this the demand for shorter delivery , high quality products and reasonable prices adds .